Desenvolvimento territorial nos perímetros irrigados do submédio do Vale do São Francisco: o caso dos perímetros Nilo Coelho e Bebedouro (PE) - Sobel, Tiago Farias (2006)
The Submedio of the San Francisco Valley, along of the last four decades, comes being object of great public investments directed to irrigated agriculture, causing a strong inflection in its standards of development. The intense social and economics impacts in the agricultural area and also in the urban way, are transforming this microregion into a great dynamic national space. In this context, this dissertation aims at to qualify and to question in which sense can be considered that the governmental performance was well succeeded in this microrregion, pointing the reasons with respect to the attainment of the observed results. In this dissertation was used the following elements: i) a bibliographical revision on the different ways of governmental performance related to the territorial development top-down and botton-up emphasizing the first strategy because it was the alternative used by the govern in the study region; ii) inform data about the economic, social, technological and organizational microregion reality, aiming at a better visualization of the principal transformation resulting from adopted public politics; e iii) interviews with the principal actors (agricultures families, communitarian leaderships, researchers, technicians, and others social actors) linked with the regional reality aiming at to have a better notion and data about it. In general, based on the gotten results, can be concluded that the intervention occurred in the studied microrregion caused significant effects in its economic development. However, this fat necessarily doesn t means a population life qualify improvement. But the recent constitution of an social capital inserted in favor of the new regional productive reality is contributing for its economic development potencialization and its transformation in social development too.